Transformacja sektorowej struktury pracujących na obszarach metropolitalnych Polski w latach 1998-2003 - Strahl, Danuta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This paper discusses changes in Polish metropolitan areas from 1998 to 2003. During this period, structural transition of four sectors of economy was very slow. Polish metropolitan areas - except Warsaw - have rather local scope but their structure of persons employed in services is similar to European metropolises' one. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 27-37